2010
DOI: 10.7863/jum.2010.29.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings of Multiple Pregnancy With a Complete Hydatidiform Mole and Coexisting Fetus

Abstract: On the basis of our experience, in cases with a normal karyotype and no gross fetal abnormalities on sonography, we carefully recommend continuation of pregnancy as long as maternal complications are absent or controllable. However, updated treatment criteria are still needed, and intensive maternal follow-up is necessary in the postpartum period because maternal complications during pregnancy and PTD after TOP are not uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 19 publications
3
44
1
1
Order By: Relevance
“…In the presence of a normal karyotype and the absence of maternal complications, continuation of pregnancy has been suggested by few researchers, because they suggest that the risk of persistent trophoblastic disease is similar to that of singleton molar pregnancies in complete mole with coexisting fetus pregnancy. [10][11][12] In cases of coexistent partial mole, the fetus is always triploid and therefore termination of pregnancy is indicated. 9 Termination of pregnancy can be achieved by suction evacuation, dilatation and evacuation, or oxytocin infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a normal karyotype and the absence of maternal complications, continuation of pregnancy has been suggested by few researchers, because they suggest that the risk of persistent trophoblastic disease is similar to that of singleton molar pregnancies in complete mole with coexisting fetus pregnancy. [10][11][12] In cases of coexistent partial mole, the fetus is always triploid and therefore termination of pregnancy is indicated. 9 Termination of pregnancy can be achieved by suction evacuation, dilatation and evacuation, or oxytocin infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of 77 CHMCTF patients, Sebire et al [8] reported successful delivery of 31 live babies. In contrast, in a recent study by Lee in 2010, only one out of six patients delivered a live baby, while five ended in pregnancy termination.…”
Section: Discussionmentioning
confidence: 99%
“…In a partial molar pregnancy, the fetus can develop but is usually malformed and nonviable, while no fetus develops in a complete molar pregnancy. Although rare, there have been a few sporadic antenatally diagnosed cases of hydatidiform mole with a coexisting diploid live fetus [3,8].…”
Section: Discussionmentioning
confidence: 99%